Photographie et cinéma chez Henri Focillon : illustrer, sérier, diffuser et enseigner. Le renouvellement d’une discipline - Lemoine, Colin (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2006)
Henri Focillon is representative of a period in art history when the reproducibility of the image was established. The exponential conditions of access to images invite us to rethink art history as a theoretical discipline animated by increasingly operative scholarly analysis. Concreteness, which brings image culture into teaching and the dissemination of knowledge, has determining foundations in photography (reproduction and circulation), in “casting” – lax vehicle and figure of the double – and cinema. Thus, after founding the medieval department of the Musée des moulages in Lyon, Focillon conceived a Bureau International de Reproduction Photographique, a veritable “database” before its time. He also researched “educational” cinema, an enterprise that was symptomatic of a “life of forms,” which found in the reproducibility of images a decisive and innovative medium.